2015
DOI: 10.1155/2015/274585
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cancer Progression: Is There a Role of Fatty Acid Metabolism?

Abstract: Currently, there is renewed interest in elucidating the metabolic characteristics of cancer and how these characteristics may be exploited as therapeutic targets. Much attention has centered on glucose, glutamine and de novo lipogenesis, yet the metabolism of fatty acids that arise from extracellular, as well as intracellular, stores as triacylglycerol has received much less attention. This review focuses on the key pathways of fatty acid metabolism, including uptake, esterification, lipolysis, and mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 207 publications
(219 reference statements)
3
71
0
5
Order By: Relevance
“…In agreement, studies in tumourbearing animals showed an increase in lipolysis and therefore an increase in the FFA release into plasma due to the hydrolysis of adipose tissue TAGs (Sakurai and Klein, 1998). Consistently, proteins that have been identified as facilitating the uptake of FAs into cells, and those involved in FA transport have also been implicated in cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). Further in support of this idea is the link between dietary FAs and breast cancer (Hsu et al, 2007).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 56%
See 2 more Smart Citations
“…In agreement, studies in tumourbearing animals showed an increase in lipolysis and therefore an increase in the FFA release into plasma due to the hydrolysis of adipose tissue TAGs (Sakurai and Klein, 1998). Consistently, proteins that have been identified as facilitating the uptake of FAs into cells, and those involved in FA transport have also been implicated in cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). Further in support of this idea is the link between dietary FAs and breast cancer (Hsu et al, 2007).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 56%
“…Several proteins such as CD36/FAT and fatty acid-binding proteins (FABPs) have been identified to facilitate the uptake of FFAs into cells. Consistent with the idea that FFAs have a role in cancer, those FA-transport proteins have also been implicated in promoting cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). The long-chain monosaturated FFA oleate has been shown to be able to stimulate the proliferation of human breast cancer cells, with PI3K having a role in this process (Hsu et al, 2007;Hardy et al, 2005).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 73%
See 1 more Smart Citation
“…The volume and composition of the adipose tissue is altered by metabolic syndrome or obesity, which may in turn influence lipid availability and utilization. While there is conflicting data on the effect of obesity on the risk of developing prostate cancer, there is now strong evidence that obese men have more aggressive disease at diagnosis and a higher rate of recurrence following surgery (reviewed in Balaban et al (2015), Taylor et al (2015)). In cell line models, lipids taken up by prostate cancer cells can drive proliferation (Nieman et al 2013) and potentially invasiveness (Sacca et al 2012).…”
Section: Androgens Stimulate Lipid Synthesis Uptake and Storagementioning
confidence: 99%
“…These alterations are characterized by redistribution of glucose carbons away from catabolism for ATP production toward macromolecule synthesis and maintenance of reductive capacity to sustain proliferation (Romero‐Garcia et al ., 2011). In addition to enhanced glucose and glutamine metabolism, alterations in cancer cell fatty acid (FA) metabolism have been reported (Balaban et al ., 2015). However, in general, these observations have predominantly been limited to the synthesis of new FAs from nonlipid carbon sources, that is, glucose and glutamine (Zhang and Du, 2012).…”
Section: Introductionmentioning
confidence: 99%